Mutational analysis of the solute carrier family 11 member 1 gene (SLC11A1) implicated in iron transport - Zaahl, Monique G. (Monique Glenda) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2003.